Ginger-derived exosome-like nanoparticles: a representative of plant-based natural nanostructured drug delivery system - Liu, Houhe; Deng, Yi; Li, Jiayan; Lin, Wen; Liu, Chongzhi; Yang, Xiaofei; Zhou, Zunzhen; Jiang, Yuan (Frontiers in Bioengineering and Biotechnology, 2025)
In recent years, the research on plant-derived exosome-like nanoparticles (PELNs) has attracted increasing attention. Among these, ginger-derived exosome-like nanoparticles (GELNs) stand out due to their specific pharmacological activity and their role as reliable carriers for delivering both hydrophilic and hydrophobic drugs, as well as small RNAs, making them a noteworthy representative of plant-based natural nanostructured drug delivery systems (DDS). In this review, we first introduce the characteristics and engineering methods of GELN-based DDS to brush up on our current understanding and then focus on research progress to summarize their therapeutic application scope and challenges.